The impact of office innovation in the physical workplace on employee and organizational outcomes - Abdul Hamed, Sapiah; Mohd. Hussain, Mohd. Ramzi; Md Jani, Haza Hanurhaza; Sabri, Syikh Sazlin Shah; Rusli, Nazrul (Semarak Ilmu Publishing, 2025)
The physical environment through office innovation influences the success of the employees and organization at the workplace. Office innovation plays a crucial role in shaping a workspace that fosters productivity, collaboration, and overall well-being. A well-designed physical workplace tailored to the specific needs of employees can enhance both individual performance and organizational outcomes. Organizations have the responsibility to create environments that not only support daily tasks but also encourage creativity, communication, and engagement. By investing in innovative office designs -such as open layouts, flexible workspaces, ergonomic furniture, and integrated technology -companies can foster a culture of collaboration and innovation. The paper analyses analytical reviews of the existing literature to explore the relationship between office innovation and its impact on employees and organizational outcomes. Content analysis of relevant studies reveals that comfortable and well-designed physical environments lead to improved employee satisfaction, engagement and retention. Additionally, a conducive workspace promotes better communication, creativity, and teamwork, all of which contribute to higher levels of organizational performance. The findings highlight the importance of creating a healthy, innovative work environment thatsupports employees in their tasks, ultimately benefiting the organization by driving success and long-term sustainability